Genetic diversity and demographic history of the giant river catfish Sperata seenghala inferred from mitochondrial DNA markers. (2nd November 2017) - Kumari, Priyanka; Pavan-Kumar, A.; Kumar, Gulshan; Alam, Absar; Parhi, Janmejay; Gireesh-Babu, P.; Chaudhari, Aparna; Krishna, Gopal
Abstract: The giant river catfish Sperata seenghala has huge demand in South Asian countries due to its low number of intramuscular bones and nutritive value. However, the culture practises for this fish have not been standardized and the current demand for this fish is being met by capture fisheries only. Unregulated and indiscriminate fishing would lead overexploitation of fish stocks subsequently stock depletion. Genetic diversity between populations would give insight about population structure and demography. In the present study, S. seenghala stocks from three rivers, namely Ganga, Brahmaputra and Mahanadi were characterized using cytochrome b gene and D-loop region. Moderate to high haplotype diversity and low nucleotide diversity values were observed in all populations. Analysis of molecular variance and pairwise F ST values showed significant genetic differentiation among populations. Patterns of diversity, haplotype networks and mismatch distribution strongly suggest a historical influence on the genetic structure of S. seenghala populations. S. seenghala stocks from these three rivers are genetically distinct units and management measures should be formulated separately for each population.